Circumstances of the discovery and the search for the deposition context of the ornamented antler artefact - Kowalski, Krzysztof; Płonka, Tomasz (Uniwersytet Wrocławski. Instytut Archeologii, 2017)
The stray find of an ornamented antler object recovered at Powalice in 2003 in anarable field improved with lake chalk quarried at the “Rusinowo” quarry (Świdwin commune,Świdwin County, West Pomeranian Voivodeship) was presented to the National Museum inSzczecin in 2004. An action taken by researchers to confirm the original place of depositionof this find recovered from a secondary deposit and to reconstruct its environmental andcultural context. The antler artefact from Rusinowo is the first piece of portable art referredto the symbolic culture of forager communities in Pomerania to have its context of depositionstudied in so much detail. Parallel to these activities the find was also subjected to physicalchemistry, earth science, technological and experimental archaeology analyses designed torecover a possibly complete body of data about its history prior to its discovery. Thanks to itsstable preservation status, lack of alteration during the modern age and the decision taken bythe Museum to delay conservation treatment, at the time of laboratory studies the antler stillretained a residue of chalk on its surface. The field prospection, interviews and the review ofthe archival documentation from the chalk quarry brought in no definitive conclusions buttaken together with the results of geological sampling and palynology studies this input corroboratedand complemented the data from the analysis of the artefact, shedding new light onthe symbolic culture of Late Palaeolithic and early Mesolithic communities of Central Europe
Keywords: stray find; finders; provenance; context of deposition; specialist analyses